Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.4049/jimmunol.177.7.4577
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Mycobacterial Phosphatidylinositol Mannoside Binding to Mouse CD1d

Abstract: Mycobacterial phosphatidylinositol tetramannosides (PIM4) are agonists for a distinct population of invariant human (Vα24) and mouse (Vα14) NKT cells, when presented by CD1d. We determined the crystal structure at 2.6-Å resolution of mouse CD1d bound to a synthetic dipalmitoyl-PIM2. Natural PIM2, which differs in its fatty acid composition is a biosynthetic precursor of PIM4, PIM6, lipomannan, and lipoarabinomannan. The PIM2 headgroup (inositol-dimannoside) is the most complex to date among all the crystalliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 57 publications
1
75
0
Order By: Relevance
“…Arg79 is conserved in CD1b and CD1d of other species and plays a key ligandbinding role in CD1d structures (23)(24)(25). However, unlike CD1d, which often holds lipid polar heads by establishing hydrogen bond interactions with several residues (23)(24)(25)(26)(27)(28), no further direct polar head-anchoring residues were found in the SGL12-loaded CD1b structure. The interaction between the SGL12 sulfotrehalose and Arg79 was solely reinforced by indirect hydrogen bonds, mediated by water molecules, with Gly76 and Gln152.…”
Section: Resultsmentioning
confidence: 89%
“…Arg79 is conserved in CD1b and CD1d of other species and plays a key ligandbinding role in CD1d structures (23)(24)(25). However, unlike CD1d, which often holds lipid polar heads by establishing hydrogen bond interactions with several residues (23)(24)(25)(26)(27)(28), no further direct polar head-anchoring residues were found in the SGL12-loaded CD1b structure. The interaction between the SGL12 sulfotrehalose and Arg79 was solely reinforced by indirect hydrogen bonds, mediated by water molecules, with Gly76 and Gln152.…”
Section: Resultsmentioning
confidence: 89%
“…We estimate that no molecule larger than a single-chain C 18 lipid molecule could fit within this pocket and still coordinate a charged head group with the conserved Arg-82 residue near the opening of the pocket. Larger head groups that project into the solvent above the pocket opening are possible, as observed for the binding of mycobacterial phosphatidylinositol mannoside with CD1d (30). However, the volume constraints of chCD1-2 protein would limit the length of any bound hydrocarbon chain.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of chCD1-2 with an endogenously bound ligand, presumably palmitic acid, was determined to a resolution of 2.0 Å [supporting information (SI) Table S1]. The overall structure of chCD1-2 resembles that of mammalian CD1 molecules (8,17,18,21,26,(30)(31)(32)(33). Briefly, 2 ␣ helices (␣1 and ␣2) sit atop a central 6-stranded, anti-parallel, ␤-sheet platform, thus forming the ␣1-␣2 superdomain.…”
Section: Resultsmentioning
confidence: 99%
“…Recent crystal structure studies of glycolipid-CD1d complexes have revealed that the lipid portion of glycolipids fits into the CD1d binding groove with some diversity (28)(29)(30)(31). Biological studies on α-GalCer analogues have shown that the modification of the lipid chain determines Th1/Th2 balance (32,33).…”
Section: Discussionmentioning
confidence: 99%